Development of methods for studying embryo-uterine interactions - Z Zhang; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1989)
The endometrium (lining of the uterus) functions to support and nurture developing embryos. However, 20 to 30% of pig embryos are lost in early pregnancy. Therefore, we developed methods to study the endometrium. Our initial work addresses the production of prostaglandins by the endometrium. Prostaglandins are known to play important roles in the establishment of pregnancy. In the pig, this process occurs near the end of the second week of pregnancy. Therefore, we determined the prostaglandin production by glandular and stromal cells of pig endometrium collected on d 13 of pregnancy. Glandular cells produced more prostaglandin F2Î± (PGF2Î±) than prostaglandin E (PGE). In contrast, stromal cells secreted more PGE than PGF2Î±. Progesterone inhibited PGE and PGF2Î± production by both glandular and stromal cells. Four-hydroxyestradiol, an estrogen produced by pig blastocysts and endometrium, inhibited PG production of both prostaglandins by glandular cells but stimulated prostaglandin production by stromal cells. Our data indicate that glandular and stromal cells of the pig endometrium possess different characteristics of prostaglandin production, and these differences may be important in conceptus signaling for the establishment and maintenance of pregnancy.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Uterus; Embryo; Pregnancy; Prostaglandin; Estrogen